Stabilizing γ-MgH2 at nanotwins in mechanically constrained nanoparticles - Kammerer, Jochen; Duan, Xiaoyang; Neubrech, Frank; Schröder, Rasmus R.; Liu, Na; Pfannmöller, Martin (Advanced materials, 2021)
Reversible hydrogen uptake and the metal/dielectric transition make the Mg/MgH2 system a prime candidate for solid-state hydrogen storage and dynamic plasmonics. However, high dehydrogenation temperatures and slow dehydrogenation hamper broad applicability. One promising strategy to improve dehydrogenation is the formation of metastable γ-MgH2. A nanoparticle (NP) design, where γ-MgH2 forms intrinsically during hydrogenation is presented and a formation mechanism based on transmission electron microscopy results is proposed. Volume expansion during hydrogenation causes compressive stress within the confined, anisotropic NPs, leading to plastic deformation of β-MgH2 via (301)β twinning. It is proposed that these twins nucleate γ-MgH2 nanolamellas, which are stabilized by residual compressive stress. Understanding this mechanism is a crucial step toward cycle-stable, Mg-based dynamic plasmonic and hydrogen-storage materials with improved dehydrogenation. It is envisioned that a more general design of confined NPs utilizes the inherent volume expansion to reform γ-MgH2 during each rehydrogenation.